Onset of pain to surgery time in acute aortic dissections type A: a mandatory factor for evaluating surgical results? - Kaufeld, Tim; Martens, Andreas; Beckmann, Erik; Rudolph, Linda; Krüger, Heike; Natanov, Ruslan; Arar, Morsi; Korte, Wilhelm; Schilling, Tobias; Haverich, Axel; Shrestha, Malakh (Frontiers in Cardiovascular Medicine, 2023)
Objective An acute aortic dissection type A (AADA) is a rare but life-threatening event [1, 2]. The mortality rate ranges between 18% to 28% and mortality is often within the first 24 hours and up to 1–2% per hour [3-6]. Although the onset of pain to surgery time has not been a relevant factor in terms of research in the field of AADA, we hypothesize that a patient’s preoperative conditions depend on the length of this time. Methods Between January 2000 and January 2018, 430 patients received surgical treatment for acute aortic dissection DeBakey type I at our tertiary referral hospital. In 11 patients, the exact time point of initial onset of pain was retrospectively not detectable. Accordingly, a total of 419 patients (67.5% male; median age: 63.5 years (y); IQR: 53.3–71.4 y) were included in the study. The cohort was categorized into two groups: Group A with an onset of pain to surgery time < 6 h (n=211) and Group B > 6h (n=208), respectively. Results Preoperative conditions differed significantly between the cohorts. Differences were detected in terms of malperfusion (A: 39.3%; B: 23.6%; P: 0.001), neurological symptoms (A: 24.2%; B: 15.4%; P: 0.024), and the dissection of supra-aortic arteries (A: 25.1%; B: 16.8%; P: 0.037). In particular, cerebral malperfusion (A 15.2%: B: 8.2%; P: 0.026) and limb malperfusion (A: 18%, B: 10.1%; P: 0.020) were significantly increased in Group A. Furthermore, Group A showed a decreased median survival time (A: 1359.0 d; B: 2247.5 d; P: 0.001), extended ventilation time (A: 53.0 h; B: 44.0 h; P: 0.249) and higher 30-day mortality rate (A: 25.1%; B: 17.3%; P: 0.051). Conclusions Patients with a short onset of pain to surgery time in cases of AADA present themselves not only with more severe preoperative symptoms but are also the more compromised cohort. Despite early presentation and emergency aortic repair, these patients show increased chances of early mortality. The “onset of pain to surgery time” should become a mandatory factor when making comparable surgical evaluations in the field of AADA.